The evolution of the day-of-the-week effect and the implications in the crude oil market - Li, Wenhui; Zhu, Qi; Wen, Fenghua; Mohd Nor, Normaziah (Elsevier BV, 2022)
The movement of prices in the crude oil market are important to the international economy and financial asset returns. Day-of- the-week effect is a great challenge to the market's effectiveness. We examine the evolution of day-of-the-week and investigate its implications based on the West Texas Intermediate crude oil return from 14 May 2007 to 14 May 2021. We have obtained convincing findings that there is abnormal positive return on Wednesdays because the inventory shock schedule. Abnormal negative return on Mondays disappears sometimes, because bad sentiment is not the only decisive factor, as it is also determined by reactions to good sentiment. The results provide implication for the day-of-the-week effect and new evidence that crude oil market's efficiency changes over time. Policy makers, investors and producers can benefit from this.